Cyclosporin A reduces airway mucus secretion and mucociliary clearance in rats (Clinics, 2007)
PURPOSE: To assay the effects of cyclosporin A on mucus secretion from goblet cells and on mucociliary transport in situ in rats. METHODS: Twenty-one male Wistar rats were assigned to 3 groups: control (n = 5), saline (n = 8), and cyclosporin A (n = 8). After 30 days of drug therapy, the rats were killed, and the lungs were removed from the thoracic cavity. Mucus samples were collected, and the transport rate was evaluated in vitro using a bullfrog palate model. Mucociliary transport was timed in situ by direct view of particles trapped on the mucus moving across the respiratory tract. Finally, the amount of stored mucins in the goblet cells of the respiratory epithelium was measured. RESULTS: Drug dosage measurements showed that cyclosporine blood concentration at the moment the rats were killed was 1246.57 ± 563.88 ng/mL. The in vitro transport rate was significantly lower (P < .001) in the cyclosporin A-treated group. Also, the in-situ mucociliary transport rate was decreased in all cyclosporin A-treated animals when compared to the saline group (P = .02). Mucus quantity measurements showed a significant decrease on both acid (P = .01) and neutral (P = .02) mucus production from goblet cells in the animals submitted to cyclosporin A therapy. The correlation between the percentage of total mucus and in vitro transport rate was positive and significant (r = 0.706, P < .001), as was the correlation between the percentage of total mucus and the in situ mucociliary transport rate (r = 0.688, P = .001). CONCLUSION: This study shows that cyclosporin A plays an important role in the impairment of the mucociliary clearance in rats by reducing both acid and neutral mucus production from goblet cells and causing a decrease in the mucociliary transport velocity.